IMPLEMENTASI PROGRAM LITERASI UNTUK MENINGKATKAN MINAT MEMBACA SISWA KELAS III SDN KABINUANG - Hikma Hikma; Moh Rudini; Saugadi Saugadi (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Literacy skills, especially reading, are a crucial foundation for successful learning in elementary schools. However, low reading interest remains a challenge, including at SDN Kabinuang, where most third-grade students prefer playing over reading. To address this issue, a literacy program was implemented using varied teaching media, including an educational film on anti-bullying, word search activities, and word puzzles. The program took place on July 25, 2025, at SDN Kabinuang, Dampal Utara District, Tolitoli Regency. The film provided a visual understanding of bullying issues, while the word search and puzzles trained concentration, logical thinking, and vocabulary enrichment. The results indicated increased student participation, learning enthusiasm, and positive attitudes toward reading. The use of varied media proved effective in creating an interactive and enjoyable learning environment while instilling positive moral values. This program aligns with the National Literacy Movement and is expected to serve as a model for effective literacy implementation in elementary schools to develop intelligent, critical, and competitive young generations in the information era.